A Monte Carlo based dose verification tool for an HDR Ir‐192 brachytherapy source and its evaluation on extremity malignancies - Peixiong Li; Chi Wah Kong; Rihui Zhang; Dejun Zhou; Chenyu Huang; Tin Lok Chiu; Pak Hang Nam; Chi To Yung; Tien Yee Chang; Siu Ki Yu; Bin Yang (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background TG‐43 formalism dose calculation for brachytherapy with the homogeneous water‐based assumption is widely used, which can lead to dose inaccuracy in treatment planning. Purpose Extremity malignancies are also treated with high‐dose‐rate (HDR) 192 Ir interstitial brachytherapy, a treatment site that has not been specifically investigated in prior comparative dosimetric studies, and the proximity of source dwell positions to bone and air introduces significant heterogeneity. BrachyPlanCheck, an in‐house brachytherapy second dose verification program for Monte Carlo (MC) simulations, incorporates these heterogeneities and is used for a comparative dosimetric study on extremity malignancies. Methods BrachyPlanCheck was commissioned and validated in both a homogeneous water phantom and a heterogeneous breast phantom. The clinical evaluation included 8 patient‐specific lower limb brachytherapy plans, comparing TG‐43 and MC calculation using BrachyPlanCheck. Dosimetric differences were evaluated using dose comparisons, gamma index analysis, and dose‐volume histogram (DVH) metrics for clinical target volume (CTV) and organ‐at‐risk (OAR), including bone and skin. Results In commissioning Level 1, MC simulations using BrachyPlanCheck demonstrated point dose agreement within ± 0.9%. Gamma passing rates exceeded 99.9% with criteria 1 mm/1% in commissioning Level 2. In clinical evaluation, TG‐43 calculation overestimated CTV V150 by up to 10.50% and CTV D90 by up to 7.25%. OAR doses were generally higher with TG‐43, with mean differences of 1.09% for bone D1cc ( p = 0.109), 1.38% for bone D0.1cc ( p = 0.078), 7.30% for skin D2cc ( p = 0.008), and 5.68% for skin D0.1cc ( p = 0.008). Conclusion Validated by phantom and patient study, BrachyPlanCheck demonstrated robust performance for independent secondary dose verification. TG‐43 calculation overestimated dose to CTV and OAR in extremity malignancy cases compared with BrachyPlanCheck.